Percutaneous Fixation of Anterior Column Acetabular Fracture in a Renal Transplant Recipient - Halil Ceylan; Ozgur Selek; Ahmet Y. Sarlak (Case Reports in Orthopedics)
Renal transplantation, performed per million population, ranges from 30 to 60 in developed countries. The transplanted kidney is generally placed in iliac fossa; therefore the treatment procedure of the pelvic trauma in these patients should be selected carefully. The gold standard technique for the treatment of displaced acetabulum fractures is open reduction and internal fixation. Our patient had received a living-related-donor renal transplant due to chronic renal failure. In the second year of transplantation, she had been injured in a motor-vehicle accident, and radiographs showed a right acetabular anterior column fracture and left pubic rami fractures. The patient was treated with percutaneous fixation techniques and at one year of postoperative period there was no evidence of degenerative signs and the clinical outcome was good. Beside having the advantage of avoiding dissection through the iliac fossa by the standard ilioinguinal approach, percutaneous techniques, with shorter surgical time, decreasing soft tissue disruption, and the potential for early discharge from hospital might be ideal for a renal transplant recipient carrying a higher risk of infection. Percutaneous fixation of selected acetabular fractures in a renal transplant recipient would presumably have the potential to decrease the morbidity associated with traditional open surgical procedures.